Islamic Economic Advantages and The Law No. 5 of 1999 in Preventing Monopoly Practices - Ahmad Munir Hamid; Ahmad Fathur Rozi; Siti Nur Mahmudah (Enrichment : Journal of Management, 2020)
Every human being has the right to distribute his property according to what he wants, whether hoarded or sold at a very high price, but if it is entered into a monopoly or ihtikar measure, the issues discussed are no longer about the right to freedom of distribution but have touched on the impact that will be caused for what was done. A monopoly which is prohibited according to religion will certainly have a major impact on the people's economy. The purpose of this study was to determine the relationship between the advantages of Islamic economics and Law No. 5/1999 in preventing monopolistic practices. This study used a qualitative descriptive method through measured interviews by informants. The result of this research is that the existence of law number 5 of 1999 has certainly provided a sense of security to business actors from monopolistic practices and unfair business competition, the form of law number 5 of 1999 also gives a message that the government through the competent agency (KPPU) is present. in an effort to control the existence of all kinds of violations that intimidate many people and benefit a few, such as monopolistic practices and unfair business competition. Even some of those contained in the anti-monopoly law also have a very strong correlation to several principles and arguments in Islamic economics, especially in the aspects of preventing monopolistic practices and unfair business competition.